MAIN APPROACHES OF THE SUPPLEMENT OF ENERGY SECURITY IN CENTRAL ASIAN COUNTRIES - Ayupova Z. K; Kussainov D. U; Kurmanalieva A. A; Sutalinova N. A; Nagan Winston (Scientific Journal of Pedagogy and Economics, 2019)
The article provides a general description of the energy sectors in Central Asia, which were created under a single system in which each State had an influence on each other’s energy security, and together they ensured the uninterrupted supply of energy resources, both for the population and for economic needs in general. A unified system involves balancing the energy interests of all countries. Reaching consensus in Soviet times did not seem to be a problem, as there was a single political center. With the independence of the countries of Central Asia, the format of relations within the framework of the Central Asian Energy System (CAES) was changed, as States prioritized the creation of independent energy systems. Over the past two decades, regional energy cooperation among Central Asian countries has been largely ignored. However, the analysis shows that the growing threats to energy security will force the leaders of the countries to reconsider their energy policy. Mitigating the possible effects of the energy crisis and ensuring a smooth transition to the energy independence of each country will require a consolidation of efforts in the energy sector. The growing problems of energy security and the lack of real prospects for the implementation of major regional projects have led Central Asian leaders to seriously consider the possibility of restoring intraregional energy trade.